The possible and intriguing relationship between bullous pemphigoid and melanoma: speculations on significance and clinical relevance - Russo, Filomena; Pira, Anna; Mariotti, Feliciana; Papaccio, Federica; Giampetruzzi, Anna Rita; Bellei, Barbara; Di Zenzo, Giovanni (Frontiers in Immunology, 2024)
Bullous pemphigoid (BP) is the most common autoimmune bullous disease: it most commonly affects individuals over 70 years old and impacts severely on their quality of life. BP represents a paradigm for an organ-specific autoimmune disease and is characterized by circulating IgG autoantibodies to hemidesmosomal components: BP180 and BP230. While the crucial role of these autoantibodies in triggering BP inflammatory cascade is fully acknowledged, many ancillary etiological mechanisms need to be elucidated yet. Cutaneous melanoma is due to a malignant transformation of skin melanocytes, that produce and distribute pigments to surrounding keratinocytes. Melanoma is the most fatal skin cancer because of its increasing incidence and its propensity to metastasize. Several data such as: i) reported cases of concomitant melanoma and BP; ii) results from association studies; iii) BP onset following immune check-point inhibitors therapy; iv) expression of BP antigens in transformed melanocytes; and vi) circulating autoantibodies to BP antigens in melanoma patients suggest an intriguing, although unproven, possible association between melanoma and BP.However, a possible causative link is still debated and the putative pathogenetic mechanism underlying this association is unclear.This review aims to describe and discuss the possible relationship between BP and melanoma and give an overview of the speculations for or against this association. Of note, if demonstrated, this association could unwrap considerations of clinical relevance that represent new research frontiers.